INOVASI METODE PENGAJARAN PAI DI ERA DIGITAL - Nurma Yunita Peu’uma (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2025)
Technology in the 4.0 era or digitalization era is experiencing such rapid development that it has an impact on all fields including Islamic education, where in the teaching system teachers must be able to innovate PAI teaching methods which up to now still seem to use conventional methods. This research aims to explore various innovative strategies that PAI teachers can use to increase the effectiveness of their teaching in the digital era. This research uses the library research method. The results of research from PAI Teaching Method Innovation in the digital era are the use of Information and Communication technology as well as the development of mobile learning applications, the use of Augmented Reality (AR) and Virtual Reality (VR) technology in learning Islamic Religious Education.